2007
DOI: 10.1029/2007je002887
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of H, Si, Cl, K, Fe, and Th in the low‐ and mid‐latitude regions of Mars

Abstract: We report maps of the concentrations of H, Si, Cl, K, Fe, and Th as determined by the Gamma Ray Spectrometer (GRS) on board the 2001 Mars Odyssey Mission for ±∼45° latitudes. The procedures by which the spectra are processed to yield quantitative concentrations are described in detail. The concentrations of elements determined over the locations of the various Mars landers generally agree well with the lander values except for Fe, although the mean of the GRS Fe data agrees well with that of Martian meteorites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
212
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 295 publications
(229 citation statements)
references
References 78 publications
16
212
0
1
Order By: Relevance
“…Although it has been suggested, there is no definitive evidence for current or past plate tectonic processes, nor have orbital remote sensing instruments detected any major provinces of the highly-evolved crustal products that we see on Earth or on the Moon [Jolliff et al, 2000]. GRS data show no suggestion that ejecta from the largest (and deepest) impact basins have compositions that differ from surrounding areas [Boynton et al, 2007]. Although there are localized regions of quartz-bearing igneous rocks [Bandfield et al, 2004;Bandfield, 2006;Christensen et al, 2005], previously observed regions of relatively high-silica, igneous "andesite" (Surface Type 2) have been more recently reinterpreted to reflect surface coatings of a silicabearing secondary mineral phase [Wyatt and McSween, 2002;Rogers and Christensen, 2007].…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Although it has been suggested, there is no definitive evidence for current or past plate tectonic processes, nor have orbital remote sensing instruments detected any major provinces of the highly-evolved crustal products that we see on Earth or on the Moon [Jolliff et al, 2000]. GRS data show no suggestion that ejecta from the largest (and deepest) impact basins have compositions that differ from surrounding areas [Boynton et al, 2007]. Although there are localized regions of quartz-bearing igneous rocks [Bandfield et al, 2004;Bandfield, 2006;Christensen et al, 2005], previously observed regions of relatively high-silica, igneous "andesite" (Surface Type 2) have been more recently reinterpreted to reflect surface coatings of a silicabearing secondary mineral phase [Wyatt and McSween, 2002;Rogers and Christensen, 2007].…”
Section: Discussionmentioning
confidence: 76%
“…Normally these elements are preferentially sequestered into a planet's crust during differentiation [Taylor and McLennan, 2009], and this is especially true for Mars, which possesses a thick and mostly ancient crust that is proportionally large with respect to the planet's total volume compared to Earth. The Gamma-Ray Spectrometer (GRS) instrument on board the 2001 Mars Odyssey spacecraft has been used to map the K and Th abundances across nearly the entire Martian surface [Boynton et al, 2007]. Here we present the first detailed Martian surface heat production and crustal heat flow maps based on unambiguous orbital geochemical measurements that show significant geographic variation in the crustal thermal reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations